Isolation and Identification of Toxoplasma gondii from Aborted Fetuses of Goats by PCR in Lorestan Province - Morad Beiranvand; Hossein Hamidinejat; Somayeh Bahrami; Mohammad Reza Tabandeh; Meysam Makki (Journal of Ardabil University of Medical Sciences)
Background: A zoonotic obligate intracellular protozoan parasite, Toxoplasma gondii, infects all warm-blooded animals as well as humans worldwide. Identification of the level of infection in intermediate hosts gives us an important data about understanding the role of this parasite in human health as well as estimating the economic loss in livestock. Therefore, the main aim of this study was the isolation and identification of T. gondii from aborted goat fetuses by PCR in Lorestan province. Methods: From autumn 2023 to summer 2024, the brain and liver of 100 goat fetuses were examined for T. gondii by PCR based on the amplification of 529 base pair fragments from repetitive regions of the parasite genome. The study was performed in three aborted fetus groups, less than 2 months, 2 to 4 months and more than 4 months. Results: From a total of 100 examined samples, conventional PCR detected the T. gondii infection in 6 (6%) and 2 of the brain and liver fetuses respectively. Conclusion: This study shows a notable level of infection in goat fetuses, and as a result, T. gondii should be considered an important agent involved in the abortion of goats in the Lorestan province of Iran. On the other side, it is necessary to pay more attention to the risk of transmission of this parasite from farmed animals to humans, especially pregnant women and people with suppressed immune system.